Perirhinal Cortex mGlu5 Receptor Activation Reduces Relapse to Methamphetamine Seeking by Restoring Novelty Salience - Peters, Jamie (Neuropsychopharmacology, 2016)
Rats that have self-administered methamphetamine (meth) under long access, but not short access, conditions do not recognize novel objects. The perirhinal cortex is critical for novelty detection, and perirhinal metabotropic glutamate 5 receptors (mGlu5) are downregulated after long-access meth. The novel positive allosteric modulator (PAM) 1-(4-(2,4-difluorophenyl) piperazin-1-yl)-2-((4-fluorobenzyl)oxy)-ethanone, or DPFE, demonstrates improved solubility compared with other mGlu5 PAMs, thus allowing brain-site-specific pharmacological studies. Infusion of DPFE into perirhinal cortex restored novel object recognition in long-access meth rats. To investigate the impact of these cognitive enhancing effects on relapse, we tested the effects of DPFE infusions into perirhinal cortex on meth-seeking under two different test conditions. In the standard cue relapse test, perirhinal DPFE infusions did not alter meth-seeking in the presence of meth cues. However, in a novel cue relapse test, wherein animals were allowed to allocate responding between a novel cue and meth-conditioned cue, perirhinal DPFE infusions shifted the pattern of responding in long-access rats toward a profile resembling short-access rats, which respond equally for novel and meth cues. Perirhinal mGlu5 are thus a promising pharmacological target for the restoration of cognitive function in meth addicts. Targeting these receptors may also reduce relapse, particularly in situations where novel stimuli compete with conditioned stimuli for control over meth seeking.